The role of blockchain technology in improving the financial performance of sports investment projects - Hassan, Ahmed K.; Ata, Sobhi Noureldin (International Journal of Innovative Research and Scientific Studies, 2025)
The research examines the financial project performance results of blockchain technology using an evaluation of 420 participants. This research investigates how each blockchain adoption parameter (Training & Development, Participation, Tracking, Programmability, Digital Services Provided, and Processes & Systems) affects financial performance indicated through Rate of Development, Applicable Financial Transactions & Systems, Investment Opportunities, Added Financial Value, and Operational Activities. An analysis demonstrates that blockchain technology generates a substantial positive connection with financial performance, which accounts for 98.7% of its total variance (R² = 0.987, F = 8216.345, p = 0.000). The key drivers influencing financial performance improvement stem from blockchain adoption factors, which include programmability (β = 0.485) and digital services provided (β = 0.378), while Tracking (β = 0.314), Participation (β = 0.256), Training & Development (β = 0.182), and Processes & Systems (β = 0.219) form the other predictive elements. Organizations that implement blockchain technology experience improvements in transparency, as well as process efficiency and financial profitability. The research findings demonstrate a critical requirement for professional training, which should target stakeholder education about blockchain technology and knowledge acquisition. The monitoring capabilities of blockchain, together with transaction cost reductions and assurance of data transparency, allow sports institutions to develop better financial stability.